Faktor-Faktor Penentu Keberhasilan Implementasi Sistem Informasi Kesehatan Ditinjau Dari Perspektif Pengguna: Tinjauan Literatur Sistematis - Widyanti, Normalia; Khoiri, Abu; Dewanto, Iwan (Jurnal Ilmiah Global Education, 2025)
The Health Information System is expected to support health development by producing quality data and information. However, in its implementation there are still obstacles, and the human factor is the most dominant obstacle. The interaction of information systems and humans gives rise to behavioral problems, so it is important to understand the factors that influence the success of SIK implementation from the user's perspective to increase the use of SIK. This research uses a literature review method from several databases. Research findings show that there are several factors that influence the success of SIK implementation, including performance expectations, business expectations, facilitating conditions, self-confidence and anxiety, social influence, information quality, intentions, attitudes, system quality, service quality, user satisfaction, and usage behavior. Understanding the factors that influence the success of Health Information System implementation will minimize the risk of failure, serve as a guide in improving the system, optimize the use of resources, ensure alignment with organizational goals, and encourage effective use of Health Information System.